(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Introduction Electrocardiogram (ECG) is important for non-invasive cardiovascular health assessment. This study was carried out to determine the mean values, normal limits and sex differences of selected electrocardiographic variables in young adults of Yoruba ethnicity. Method One thousand apparently healthy volunteers (500 males and 500 females) aged 18 to 40 years participated in the study. Ethical approval was obtained from the Institute of Public Health of the University. Standard 12-lead resting ECG of each participant was obtained according to standard protocol After a period of rest of 5 minutes, the chest and extremities of each participant were exposed for limb and chest electrodes placement. The ECG printouts were analyzed. Descriptive variables were expressed as means± standard deviation. The lower and upper limits were determined using 5th and 95th percentile respectively. The comparison of the mean values of the male and female variables was done using the Student t-test. A p-value less than 0.05 was considered statistically significant. Results The results showed that the mean heart rate, QT interval, QTc interval, QRS duration, PR interval were 70.56 ± 10.99 bpm, 0.36 ± 0.03 s, 0.38 ± 0.03 s, 0.07 ± 0.01 s and 0.16 ± 0.02 s, respectively. There was a statistically significant difference in the heart rate, QTc and QRS duration of males and females. Conclusion Among young adults of Yoruba ethnicity, sex differences exist with regard to heart rate, QT interval, QTc and QRS duration and these should be taken into consideration in ECG interpretation.